2021
DOI: 10.1111/nph.17537
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in maize (Zea mays) influences rates of soil organic matter mineralization and gross nitrification

Abstract: Genotypic variation in maize (Zea mays) influences rates of soil organic matter mineralisation and gross nitrification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…Variation in SOM mineralization rates under plants is usually attributed to rhizosphere priming effects, where the exudation of organic compounds and root turnover affects microbial activity and use of SOM as substrate (Kuzyakov et al 2000). While factors such as root physical impacts on soil structure, nutrient and water availabilities may also affect microbial activity, our results are consistent with differential priming impacts among inbred lines (Mwafulirwa et al 2021). Increasing root diameter is commonly associated with increased rates of exudation, resulting from greater photo assimilate supply to thicker roots (Han et al 2020;Zai et al 2021).…”
Section: Study (Gwas)supporting
confidence: 85%
See 2 more Smart Citations
“…Variation in SOM mineralization rates under plants is usually attributed to rhizosphere priming effects, where the exudation of organic compounds and root turnover affects microbial activity and use of SOM as substrate (Kuzyakov et al 2000). While factors such as root physical impacts on soil structure, nutrient and water availabilities may also affect microbial activity, our results are consistent with differential priming impacts among inbred lines (Mwafulirwa et al 2021). Increasing root diameter is commonly associated with increased rates of exudation, resulting from greater photo assimilate supply to thicker roots (Han et al 2020;Zai et al 2021).…”
Section: Study (Gwas)supporting
confidence: 85%
“…SBM and RBM were determined based on harvest dry weight (V3 growth stage) at 29 days after planting (shoots were cut at the soil surface and roots were carefully removed from the soil and washed in deionized water). Fresh roots were scanned, and root length and average root diameter measured using WINrhizo (Mwafulirwa et al 2021). To explore the plant traits that could significantly explain the variation in SOM-C mineralization, correlation and stepwise multiple linear regression (SMLR) analyses were conducted for all genotypes (lines and hybrids) and for lines or hybrids separately.…”
Section: Study (Gwas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is known that the growth of plants can alter (via rhizodeposition) this microbially mediated SOM decomposition to varying extents (e.g. Cheng et al 2003;Mwafulirwa et al 2016Mwafulirwa et al , 2021, with increases of up to 380% relative to unplanted soil reported by Cheng et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, greater mass of mucilage exuded by chickpea roots were linked with the formation of larger and more porous rhizosheaths capable of storing more soil moisture in drought tolerant cultivars 27 . In annual crops such as wheat, barley and maize, there is evidence of the remarkable plant genetic influence in the formation of rhizosheath and the processes of rhizodeposition influencing rhizosphere microbial activities 18 , 28 30 , however few studies have aimed to dissect the genetics underlying the conformation of this extended root phenotype 18 , 28 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%